2017
DOI: 10.12669/pjms.333.12483
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of recombinant human brain natriuretic peptide in the treatment of acute myocardial infarction in elderly in combination with cardiac failure

Abstract: Objective:To investigate the effects and safety of recombinant human brain natriuretic peptide (rhBNP) in the treatment of elderly acute myocardial infarction induced cardiac failure.Methods:One hundred and forty-six patients who were diagnosed as elderly acute myocardial infarction induced cardiac failure in the hospital from July 2014 to July 2015 were selected. They were divided into a test group and a control group, 73 each. Patients in both groups were given conventional treatment such as stabilization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…Xu et al suggested the role of BNP elevation in ACS prognosis. 15 These results corroborate our own. In previous researches, BNP was found to be a reliable and self-determining prognostic marker in subjects with all categories of ACS [16][17][18] when assessed upon arrival at the hospital.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 91%
“…Xu et al suggested the role of BNP elevation in ACS prognosis. 15 These results corroborate our own. In previous researches, BNP was found to be a reliable and self-determining prognostic marker in subjects with all categories of ACS [16][17][18] when assessed upon arrival at the hospital.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 91%
“…Our previous research demonstrated that the serum concentration of NT-proBNP was significantly positively correlated with the severity of myocardial dysfunction and mortality [6]. Based on basic and clinical studies, the protective effects and safety of rhBNP administration during acute myocardial infarctions, acute heart failure, and the perioperative period of cardiac surgery have gradually been recognized, which provides the theoretical basis for our research [7,26,27]. In the present study, the administration of rhBNP significantly alleviated the severity of PRMD, myocardial inflammatory response, and myocardial tissue injuries, as reflected by improvements in MAP, ETCO 2 , EF, CO, and MPI values, myocardial inflammatory factors (IL-6 and TNF-α), serum levels of NT-proBNP, and myocardial tissue morphological injuries.…”
Section: Discussionmentioning
confidence: 90%
“…Recombinant human brain natriuretic peptide (rhBNP), a man-made peptide developed through gene engineering, has been widely used to treat acute heart failure induced by various causes. Research has suggested that rhBNP administration was able to significantly lower the serum concentrations of cardiac troponin T and NT-proBNP and improve myocardial function in patients with acute myocardial infarctions [7][8][9]. However, the protective effects of rhBNP on PRMD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10 studies involving 870 participants were included in the meta-analysis. 14,[20][21][22][23][24][25][26][27][28] The study selection process is shown in Figure 1. Table 1 shows the basic characteristics of the 10 included studies.…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%